2019
DOI: 10.1080/03004430.2019.1582034
|View full text |Cite
|
Sign up to set email alerts
|

Sleep-wake behaviour during the first 12 months of life and associated factors: a systematic review

Abstract: This paper aims to provide a systematic review of the literature on the associated factors with infant sleep-wake behaviour during the first 12 months of life, namely (1) the factors positively and negatively associated with sleep-wake behaviour and (2) the factors positively and negatively affected by sleep-wake behaviour. This systematic review was based on a standard protocol constructed according with the Preferred Reporting Items for Systematic Reviews and Meta-Analysis (PRISMA) statement and included 146… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 157 publications
(209 reference statements)
1
6
0
Order By: Relevance
“…While we were unable to directly test the association in this study, nighttime sleep latency, often discussed as bedtime resistance, has been previously related to paternal involvement in bedtime routines (Ragni et al., 2019). This may then speak to paternal involvement in parenting and the home environment, many aspects of which have been linked to differences in infant sleep (review in Dias & Figueiredo, 2019), and should be investigated in future research as an avenue for a potential cascade of biological effects. Moreover, infant sleep problems have been found to correlate with subsequent behavioral problems and maternal depression in the preschool years (Lam et al., 2003), perhaps suggesting that this epigenetic mark may have relevance as an infant biomarker of future problems and burden on caregivers.…”
Section: Discussionmentioning
confidence: 99%
“…While we were unable to directly test the association in this study, nighttime sleep latency, often discussed as bedtime resistance, has been previously related to paternal involvement in bedtime routines (Ragni et al., 2019). This may then speak to paternal involvement in parenting and the home environment, many aspects of which have been linked to differences in infant sleep (review in Dias & Figueiredo, 2019), and should be investigated in future research as an avenue for a potential cascade of biological effects. Moreover, infant sleep problems have been found to correlate with subsequent behavioral problems and maternal depression in the preschool years (Lam et al., 2003), perhaps suggesting that this epigenetic mark may have relevance as an infant biomarker of future problems and burden on caregivers.…”
Section: Discussionmentioning
confidence: 99%
“…The present study showed that unsettled sleep in boys is associated with a stronger increase in maternal depression symptoms than unsettled sleep in girls. Previous research has already shown that boys present more sleep difficulties than girls (Dias & Figueiredo, 2020) and that the sleep of boys is more affected by maternal depression symptoms than the sleep of girls (Beeghly et al., 2017; Netsi et al., 2015). A possible explanation for the present study’s results is that in face of the increased sleep difficulties of their sons, mothers of boys may present an increased difficulty in dealing with their infants’ sleep routines, leading to lower maternal self‐efficacy perception and increased postpartum depression symptoms (Falah‐Hassani, Shiri, & Dennis, 2016).…”
Section: Discussionmentioning
confidence: 97%
“…In an Australian longitudinal study of 376 children between two and 24 months of age, 25% of parents reported cry-fuss/sleep problems combined at least once, while they persisted in 6% over at least three-time points [20]. In infancy as well as in toddler and preschool years, sleep problems are associated with short-and long-term impaired regulatory capacity, which is associated with crying [4,15,[21][22][23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%